LOCAL CHARACTERISTICS OF SURKHAN OASIS CRAFTSMANSHIP (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article analyzes the processes of change in the local characteristics of oasis handicrafts from the southern regions of Uzbekistan, i.e. Surkhandarya region, in the 1950s-1980s. Also, the achievements in the fields of pottery, weaving and handicrafts, as well as the disappearance of traditional trends in these crafts, are highlighted on the basis of scientific literature, periodical press and archival materials.